Deformation mechanism of the explosive degradation of heavy metal azides under pulsed treatments - Lisitsyn V. M. Viktor Mikhailovich; Zhuravlev Yu. N.; Oleshko V. I. Vladimir Ivanovich; Fedorov D. G.; Tsipilev V. P. Vladimir Papilovich (2006, 2006)
Title screen